Access My Info: measuring data access rights around the world - Parsons, Christopher; Molnar, Adam; Tsui, Lokman; Kim, Kelly; Rosadi, Sinta Dewi; Zulhuda, Sonny (2019)
In 2014, the Citizen Lab and Open Effect started Access My Info (AMI) a research project that uses data access requests and complementary policy, legal, and technical methods to learn about how private companies collect, retain, process, and disclose individuals’ personal data. Accompanying the research methodology is a web-based tool that helps members of the public generate data access requests based on templates tailored to different industries.